Nutritional Innovation Using Green Seaweed (Ulva sp.) and Garlic Powder Extracts for White‐Leg Shrimp (Litopenaeus vannamei) Challenged by Vibrio harveyi - Nashwa Abdel‐Razek; Riad H. Khalil; Abeer A. M. Afifi; Afrah F. Alkhuriji; Dina M. Metwally (Veterinary Medicine and Science)
ABSTRACT This study aimed to determine the antimicrobial effects of ethanolic extracts of Ulva sp. and garlic (Allium sativum) powder ethanolic extracts against Vibrio harveyi in vitro. The stimulatory effects of Ulva sp. extract (UE) and garlic powder extract (GPE) on the growth performance and innate immune responses of white‐leg shrimp, Litopenaeus vannamei, and their challenge against V. harveyi infection were also investigated. A commercial shrimp diet (36.1% protein) was enriched with 0.5, 1.0 and 2.0 g UE/kg diet and 2, 4 and 6 g GPE/kg diet, whereas the control group was free of any supplement. Health juveniles of L. vannamei (average weight 2–3 g) were distributed in 21 fiberglass reinforced plastic (FRP) tanks (500‐L capacity) at a stocking density of 300 animals/tank to represent each treatment in triplicate. The animals were fed ad libitum on the experimental diets up to satiety four times daily for 60 days. The phytochemical analysis of ethanolic extracts of Ulva sp. and garlic powder evoked their richness of several bioactive compounds showing significant antibacterial activity against V. harveyi. The GPE exhibited a higher inhibition zone than that of the UE. The supplemented diets did not significantly affect weight gain %, final weight, feed conversion ratio, specific growth rate and survival rates of white shrimp compared to those fed on the control diet. Significant increases were observed in total haemocyte count, phagocytosis and phagocytic index of all treatments compared with the control group. There were significant increases in serum total protein, acid phosphatase activity, alkaline phosphatase, lysosomal enzyme activity, phenoloxidase activity and superoxide dismutase activity with offered diets with increasing the levels of ethanolic extracts of Ulva sp. and garlic powder up to 2.0 g UE/kg diet and 6 g GPE/kg diet, respectively. The ethanolic extraction of Ulva sp. and garlic powder‐supplemented diet groups, particularly at treatments of 2.0 and 6 g GPE/kg diet, respectively, significantly reduced the shrimp mortality induced by V. harveyi infection when compared with the control group. The net results evoked that ethanolic extraction of Ulva sp. (2.0 g UE/kg) and garlic powder (6 g GPE/kg diet) enhanced the immune response and disease resistance of the white‐leg shrimp, L. vannamei. It is also noted that the GPE is more efficient than the UE in vitro and in vivo investigations.